Pengaruh Radius Mooring Line Terhadap Penambatan Fpso Menggunakan Pendekatan Numerik - Adhitya Arya Prayudha Kurniawan (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Floating Production Storage and Offloading (FPSO) is a floating facility in the form of a ship that is used to produce as well as a temporary storage of petroleum taken in the middle of the ocean, in its operation the FPSO is moored using mooring ropes to limit the motion of the facility. This mooring system is needed to reduce dynamic movements due to environmental loads received by the FPSO. This study was conducted to analyze the motion characteristics of FPSO that have been moored using a Spread Mooring System with a certain mooring radius and the stresses received by each mooring line using a time domain based numerical approach. The method used is a literature study and a numerical approach with the Boundary Element Method (BEM), it is concluded that the further the radius of the mooring line, the smaller the tension received by each mooring rope so that the structure becomes more stable.